Análise Morfológica Comparativa da Carcinogênese Química Cutânea entre Camundongo (Mus Musculus) e Gerbilho (Meriones Unguiculatos) - Guzmán Silva, Maria Angélica (2023)
The reaction of the gerbil’s skin to the Chemical induetion of tumors was studied, comparing the early morphologic alterations ocurring in the gerbil to the ones we have also studied in the mouse. Two models of carcinogenesis were used: the cumulative with methylcholanthrene and the biphasic using methylcolanthrene as initiator, followed by croton oil as promoter. The gross findings, such as thickening of the skin and hyperemia induced by the various experiments above, were less evident in the gerbils. The microscopic findings of hyperplasia and inflammatory reaction, were aIso less intense in the gerbii's skin. The cellular proliferation wassimulated, as shown by increased mitotic rate, without any recognizable progressiva hyperplasia of the epidermis with the cumulative modelelectron microscopy displayed a less evident dilatation of intercellular space in the interfollicular epidermis of gerbils than that observed in mice, and the induction of "dark cells" was not registered in gerbils, up to the 10th week of treatment. Gerbils did not show any "dark cell" with the biphasic model, and the initial minimal dilatation of the intercellular space disappeared despite the continuing treatment It has been demonstrated that the skin of the gerbil is more resistant to chemical carcinogenesis than that of the mouse. Gerbils did not develop any papiloma up to the 30th week of treatment with the biphasic model, while mice developed such tumors after a seven-week latency period. With the cumulative model, both gerbil and mouse each developed one papilloma, but the latter did so after ten weeks of treatment, while the former took fifteen weeks. The results suggest that the relative resistence of the gerbil’s skin to Chemical carcinogenesis in based upon and adaptation to the promotion process, specially with the croton oil.